(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
In this research, the effect of different concentrations of Lavender oil on the growth of was studied Fusarium oxysporum،Acremonium strictum and all studied concentrations showed a clear inhibitory effect against this fungus.The inhibitory activity varied according to the different concentrations The concentrations (0.06-0.04-0.03-0.02-0.01 ml/g) ) showed 100% inhibition against A. strictum and the inhibition percentage was 64.51% at 0.002ml/g and 58.04% ،35.48% 12.9at a concentration of (0.004،0.002،0.001 ml/g) on the seventh day of incubation. The concentrations (0.06-0.04-0.03-0.02-0.01-0.006-0.004-0.002 ml/g) showed 100% inhibition against Fusarium oxysporum and the inhibition percentage was38.82% at 0.001ml/g on the seventh day of incubation. The inhibitory activity varied according to the different concentrations (0.06-0.04-0.03-0.02-0.01-0.006-0.002-0.001 ml/g) ) showed 100% inhibition against A. strictum and the inhibition The lethal concentration (MBC) value of Lavender oil against A. strictum was 0.01 ml/g And the inhibitory concentration (MIC) was 0.02 ml/g while the inhibitory concentration (MIC)and the lethal concentration (MBC) against F.oxysporum were 0.002 ml/g